An autopsy case of refractory vasculo-Behçet's disease. Issue 2 (March 2015) - Kaieda, Shinjiro; Zaizen, Yoshiaki; Nomura, Yoriko; Okabe, Koki; Honda, Seiyo; Kage, Masayoshi; Ida, Hiroaki; Hoshino, Tomoaki; Fukuda, Takaaki
Abstract Pulmonary vascular involvement in Behçet's disease is a rare complication with a poor prognosis. We present an autopsy case of vasculo-Behçet's disease complicated by pulmonary hemorrhage, possibly caused by rupture of pulmonary artery aneurysms. The patient was treated with a combination of high-dose steroids and pulse cyclophosphamide, but he died from massive hemoptysis. This case highlights the need for potent new therapies for patients with vasculo-Behçet's disease refractory to conventional immunosuppressive therapy, such as a combination of steroids and cyclophosphamide.